2018
DOI: 10.1007/s00204-018-2274-0
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic fate of fenclozic acid in chimeric mice with a humanized liver

Abstract: The metabolic fate of the human hepatotoxin fenclozic acid ([2-(4-chlorophenyl)-1,3-thiazol-4-yl]acetic acid) (Myalex) was studied in normal and bile-cannulated chimeric mice with a humanized liver, following oral administration of 10 mg/kg. This in vivo animal model was investigated to assess its utility to study “human” metabolism of fenclozic acid, and in particular to explore the formation of electrophilic reactive metabolites (RMs), potentially unique to humans. Metabolism was extensive, particularly invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…As mentioned above, TEM analyses reassured the formation of bile canaliculi in between xenotransplanted hepatocyte, which then networks to the intrahepatic bile ductules, namely Canals of Herring, followed by further connections to the intrahepatic bile duct. 52,59,60 Consequently, the composition of human hepatocytes-derived bile acid in the gall bladder of HLCM shows a positive correlation to the degree of RI. 61 This structural and functional re-establishment of the bile excretion machinery is particularly important for the in vivo study of xenobiotic metabolism, as the physiological biliary excretion system is an essential route for the elimination of drug metabolites.…”
Section: Recreation Of Human Liver Physiology At the Organ System Levmentioning
confidence: 96%
“…As mentioned above, TEM analyses reassured the formation of bile canaliculi in between xenotransplanted hepatocyte, which then networks to the intrahepatic bile ductules, namely Canals of Herring, followed by further connections to the intrahepatic bile duct. 52,59,60 Consequently, the composition of human hepatocytes-derived bile acid in the gall bladder of HLCM shows a positive correlation to the degree of RI. 61 This structural and functional re-establishment of the bile excretion machinery is particularly important for the in vivo study of xenobiotic metabolism, as the physiological biliary excretion system is an essential route for the elimination of drug metabolites.…”
Section: Recreation Of Human Liver Physiology At the Organ System Levmentioning
confidence: 96%
“…The authors found a dose-dependent liver toxicity in chimeric mice with a humanized liver as compared with non-humanized mice. Although currently most chimeric mice with humanized liver models used in hepatotoxicity testing (including the works of Kakuni et al and Xu et al mentioned above) were generated by transplanting PHHs [ 133 135 ], the use of stem cells to serve as hepatocyte sources for chimeric mice with a humanized liver is promising because stem cells are easily obtained and can be large-scale produced [ 136 ] (Fig. 1 ).…”
Section: Hepatocyte-like Cell Models For Hepatotoxicity Testingmentioning
confidence: 99%
“…It has been reported that humanized mouse livers show some features of human gene expression patterns and mirror responses of human liver to hepatotoxic drugs (Go 2018). In a recent issue of the Archives of Toxicology, Anja Ekdahl and colleagues used chimeric mice with humanized livers to study the metabolism of fenclozic acid (Ekdahl et al 2018). Fenclozic acid was developed as an alternative to high-dose therapy with aspirin (Chalmers et al 1969a, b).…”
mentioning
confidence: 99%
“…Fenclozic acid was developed as an alternative to high-dose therapy with aspirin (Chalmers et al 1969a, b). Although fenclozic acid showed a good safety profile in experimental animals, it had to be withdrawn from late-stage clinical development because of hepatotoxicity (Ekdahl et al 2018;Alcock 1970;Hart et al 1970). The study was performed following oral administration of 10 mg fenclozic acid per kg body weight in bile-cannulated humanized mice (Ekdahl et al 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation